METODE PRISMA DALAM MENGKAJI APLIKASI PENGARSIPAN DIGITAL - Amir Ma’ruf; Catur Susaningsih; Mila Rosmaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological advancements have driven the transformation of archiving systems from conventional methods to more efficient digital systems. This research aims to systematically review previous studies discussing digital archiving applications, with a focus on the methods and approaches used. The review process was conducted using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method, with journal selection based on relevant keywords. The results indicate that the Technology Acceptance Model (TAM) is the most frequently used method in analyzing digital archiving applications, followed by UTAUT, EUCS, and Phenomenology. Furthermore, quantitative approaches are more dominant than qualitative approaches in evaluating the effectiveness and acceptance of digital archiving systems. Key factors influencing the successful implementation of these applications include ease of use, user satisfaction, and system effectiveness. Based on the research findings, it is recommended that future studies expand the scope of literature and combine quantitative and qualitative approaches to obtain more comprehensive results. The development of digital archiving applications should also consider aspects of usability, data security, and system effectiveness to more optimally support efficient archive management.